The Managing Director's Global Policy Agenda, Spring Meetings 2022. (Policy Papers; Policy Paper, 2022)
The global policy agenda that follows recalibrates priorities to meet the new reality we are facing. The IMF also continues to adjust to respond to the rapidly evolving needs of our membership. Our flexibility has been evident over the past two years of the COVID crisis: unprecedented emergency financing; a historic Special Drawing Rights (SDR) allocation; an innovative plan to end the pandemic. Now, as we face another crisis on top of a crisis, we will continue to step up and support our member countries in every way we can-with financial resources, policy advice, and capacity development-working in collaboration with our international partners.